2018
DOI: 10.1186/s13578-018-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC15 promotes melanoma progression by epigenetically regulating PDCD4

Abstract: BackgroundLong non-coding RNAs (LncRNAs) have been identified as critical regulators in a variety of cancer types. Cancer susceptibility candidate 15 (CASC15), a lncRNA located at chromosome 6p22.3, has been discovered to participate in melanoma progression and phenotype switching. Nevertheless, the roles and molecular mechanisms of CASC15 in melanoma are far from being understood.ResultsWe found that CASC15 expression was up-regulated in melanoma tissues and associated with advanced pathological stages. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Emerging researches have reported that large number of lncRNAs are deregulated in human cancers 1820. These differentially expressed lncRNAs are closely contributed to tumor growth, metastasis, apoptosis or diagnosis, acting as antioncogenes or oncogenes 2123. In addition, LINC00662 was significantly upregulated in lung squamous carcinoma compared with lung adenocarcinoma,12 and increased in nasopharyngeal carcinoma 14.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging researches have reported that large number of lncRNAs are deregulated in human cancers 1820. These differentially expressed lncRNAs are closely contributed to tumor growth, metastasis, apoptosis or diagnosis, acting as antioncogenes or oncogenes 2123. In addition, LINC00662 was significantly upregulated in lung squamous carcinoma compared with lung adenocarcinoma,12 and increased in nasopharyngeal carcinoma 14.…”
Section: Discussionmentioning
confidence: 99%
“…29 For instance, the broad tendency of lncRNAs existing in nucleus is to interact with genomic DNA, transcription factors, spliceosomes, chromatin regulators, and so on, implicating in transcriptional and epigenetic regulations containing histone modifications. 30 Regulatory ncRNAs such as PCAT6, 31 LINC00968, 32 TUG1, 33 and CASC15 34 were reported to interact with EZH2, increasing F I G U R E 3 OIP5-AS1 represses NLRP6 expression by recruiting EZH2, increasing the H3K27me3 enrichment of NLRP6 promoter. A, qRT-PCR assay interrogated EZH2 mRNA level after transfection of pcDNA3.1 or pcDNA3.1/EZH2 into AGS and SGC7901 cells.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2, a vital catalytic subunit of PRC2, is a histone methyltransferase that epigenetically represses gene expression by promoting histone H3 lysine 27 trimethylation (H3 K27me3) [ 28 , 29 ]. PDCD4, a tumor suppressor, was recently demonstrated to be negatively regulated by CASC15, via recruiting EZH2 and subsequently changing H3 K27me3 level in melanoma [ 30 ]. Therefore, we further investigated whether TUG1 could regulate PDCD4 expression by recruiting EZH2.…”
Section: Discussionmentioning
confidence: 99%